The Expression of Hippocampal NRG1/ErbB4 Correlates With Neuronal Apoptosis, but Not With Glial Activation During Chronic Cerebral Hypoperfusion - Hei, Yue; Chen, Rong; Yi, Xicai; Wei, Lizhou; Long, Qianfa; Liu, Weiping (Frontiers in Aging Neuroscience, 2018)
Permanent bilateral common carotid occlusion (2VO) is well-established to investigate the chronic cerebral hypoperfusion (CCH)-induced cognitive deficits. Besides, previous studies suggested that disturbance of NRG1/ErbB4 signaling is associated with cognitive impairments, as well as neuronal apoptosis and neuroinflammation in CNS. However, the expression pattern of hippocampal NRG1/ErbB4 has not been systematically investigated during CCH. Here we aim to investigate the temporal changes of hippocampal NRG1/ErbB4 during CCH and their possible relationship with neuronal apoptosis and glial activation. Morris water maze (MWM) and Radial arm water maze (RAWM) tests were used to analyze cognitive impairment in 2VO rats at 28 d post-surgery, and Enzyme-linked immunosorbent assay, western blotting and immunostaining were performed at different time points (24h, 7d, 14d, 28d) to detect the expression pattern of NRG1/ErbB4 and the distribution of ErbB4. NeuN, NeuN/TUNEL, Iba1 and GFAP immunostaining and caspase activity in hippocampal CA1 subarea were assessed during CCH as well. We found that the expression of NRG1 and phosphorylated ErbB4 (pErbB4)/ErbB4 changed in a time-dependent manner (up-regulated in the acute phase and then decreased in the chronic phase of CCH). Besides, ErbB4-expressed neurons and selective types of GABAergic cells decreased after CCH, but the distribution pattern of ErbB4 remained unchanged. In addition, the expression of hippocampal NRG1/ErbB4 positively correlated with the level of neuronal apoptosis (both NeuN/TUNEL immunostaining and caspase-3 activity), but not with glial activation according to Pearson’s correlation. These findings indicated that hippocampal NRG1/ErbB4 may be involved in the pathogenesis of CCH, especially neuronal apoptosis during CCH.